Pengaruh Implementasi Digitalisasi Akuntansi dan Penggunaan Inovasi Fintech Terhadap Efisiensi Keuangan dengan Persaingan Teknologi sebagai Variabel Moderasi - Jamilatul Uyun; Nailah Aka Kusuma (Jurnal Akuntansi dan Keuangan, 2025)
This study aims to analyze the influence of the implementation of accounting digitalization and the use of Financial Technology (FinTech) innovation on financial efficiency with technology competition as a moderation variable. The population in this study is batik micro, small, and medium enterprises (MSMEs). The sample was determined by the purposive sampling method so that 234 respondents who were relevant to the research criteria were obtained. Data were collected through questionnaire deployment and analyzed using SEMPLS with hypothesis test with moderation test to determine the role of technology competition. The results of the study show that the implementation of accounting digitalization, the use of fintech innovation and technological competition directly have a significant positive effect on financial efficiency. In addition, the variable of technological competition cannot moderate the relationship by weakening the influence of accounting and FinTech digitalization on financial efficiency. These findings provide theoretical contributions, practical implications for MSMEs, management, and regulators in increasing competitiveness through the use of digital financial technology.